Enhancing Student Mathematical Proficiency through Planimetry and Digital Technologies - Liudmyla Hetmanenko (Qubahan Academic Journal)
Active societal development drives the dynamics of educational approaches to acquiring fundamental knowledge and skills by learners. The necessity of integrating innovative pedagogical technologies into mathematical curricula is prompted by changes in the general processes of perception and thinking among students, as well as the need to adapt educational strategies to these dynamics. The research assesses the impact of planimetric methods and technologies on geometry learning. The research methods used were analysis of literature, pedagogical experiments, and questionnaires of students and teachers. The outcome revealed that incorporating digital technologies and interactive activities enhances the learning of geometrical concepts and boosts students' interest. The results also indicated that the group of students who underwent instructions in line with the study's research hypotheses provided higher solutions to geometric problems than the control group. Questionnaires supported the positive attitude of students and teachers towards the new approaches, noting the enhanced comprehension of the matter and the enhanced interest in the materials. The practical value of the results is in elaborating the methodological recommendations for using digital technologies and planimetric methods in the educational process, which may help enhance the quality of mathematics instruction. Some of the drawbacks of the current study include the generalisability of the results, which suggests the importance of further optimising the ratio of traditional and new teachings applied in the study. The further development direction of the examined field of study is the fine-tuning of the approaches to using technology-enhanced learning activities to boost the efficiency of the teaching-learning process.